2002
DOI: 10.1046/j.0003-2409.2001.02393.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of ropivacaine compared with ropivacaine 
plus sufentanil for postoperative analgesia after 
major knee surgery

Abstract: SummaryThis study compared the analgesic ef®cacy of an epidural infusion of ropivacaine and ropivacaine with sufentanil following major knee surgery. In a double-blind clinical trial, 115 adult patients received either epidural ropivacaine (R group, 2 mg.ml), or ropivacaine (2 mg.ml) with sufentanil (RS group, 1 lg.ml )1 ), using a patient-controlled epidural analgesia technique. Pain scores (visual analogue scale, VAS, and the simple descriptive scale, SDS), side-effects, motor block and treatment quality wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 15 publications
1
31
0
Order By: Relevance
“…Although epidural analgesia has been considered the gold standard for pain management after TKR, some studies have shown that many patients suffer various side effects after epidural blockade. Frequent adverse effects include urinary retention, pruritus, hypotension, nausea and vomiting [1][2][3], and at least one side effects occurs in 58-87% of patients [1,2].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although epidural analgesia has been considered the gold standard for pain management after TKR, some studies have shown that many patients suffer various side effects after epidural blockade. Frequent adverse effects include urinary retention, pruritus, hypotension, nausea and vomiting [1][2][3], and at least one side effects occurs in 58-87% of patients [1,2].…”
Section: Resultsmentioning
confidence: 99%
“…The addition of opioids to local anesthetics for epidural blockade also causes postoperative nausea and vomiting [2]. In comparison, peripheral nerve block provides a more localized neural blockade.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(4,5) Using opioid as additive to local anaesthetic provides a dose sparing effect of local anaesthetic and superior analgesia, but there is an increased chances of side effects such as nausea, vomiting, pruritus, urinary retention and respiratory depression. (6,7,8) Dexmedetomidine (8,9,10) with selective α2-adrenoceptor agonist used as adjuvant to regional anaesthesia showed analgesic, sedative, anxiolytic, sympatholytic properties and causes minimal respiratory depression. Dexmedetomidine produces manageable hypotension and bradycardia without opioid-related side effects like pruritus, urinary retention, vomiting and respiratory depression.…”
mentioning
confidence: 99%